Integration of English Songs as Learning Media for the Improvement of Descriptive Writing - Inzhagi, Muh. Aditya; Sunra, La; Muhalim, Muhalim (PT ARRUS Intelektual Indonesia, 2025)
This study examines the effectiveness of English songs in enhancing students' descriptive writing skills in a senior high school in Takalar, involving 36 tenth-grade students. A pre-experimental design was utilized, incorporating pre-tests and post-tests to assess writing performance before and after the intervention. Results showed a significant improvement, with average post-test scores increasing from 63.8 to 82.6. Paired t-test analysis confirmed this enhancement, revealing a mean difference of 18 points and a t-value of 6.066 (p < 0.05). The N-Gain score of 0.46 indicates moderate overall improvement. These findings suggest that English songs serve as effective authentic materials, engaging students and improving their content organization, vocabulary usage, and grammatical accuracy, particularly in the simple present tense. This research underscores the value of using English songs as a teaching tool to enhance descriptive writing skills, offering valuable insights for educators.